Imagens de um Brasil profundo : uma história revisitada de Vidas secas, Deus e o diabo na terra do sol e Os fuzis - José Antônio de Souza Queiroz (2019)
The present historical research aims to clarify the terms under which consolidated the rapprochement between the literary and cinematic languages throughout the first stage of the Cinema Novo movement. For this, the research will centralize the analysis in three deep literary movies: Vidas Secas (1963), by Nelson Pereira dos Santos; Deus e o Diabo na Terra do Sol (1964) by Glauber Rocha and Os Fuzis (1964), directed by Ruy Guerra. The premise is that, especially, from the dialogue with literature, these directors were able to carry out complex works in terms of temporality, in the elaboration of images that open the history of Brazil in search of references to understanding the political disputes of the early 1960. The thesis is that the Cinema Novo found in certain Brazilian authors, not just thematic elements and plot, but the thrust of political activism, and the required sensibility to discover and discuss Brazil in their movies.